Um (novo) Porto do Capim para um rio de difícil navegação: trabalhadores e as margens da modernização urbana na cidade da Parahyba (1920-1924) - Teles, Letícia Helen Silva (2022)
In a conjuncture marked by clientelism and conflicts between sectors of the dominant class for the direction of hegemonic power of the state, the attempt to restructure the Porto do Capim in the 1920s presented itself as a paradise of easy business, characterized by the diversion of public funds. Inserting itself in the first phase of capitalist modernization in Parahyba, port works were carried out in a context of attempts to order and sanitize a city that, as mentioned by Mario de Andrade (1929), was and continued to be "disassembled with everything mixed in". During this process, central peripheries continue to emerge in the city's dens through streets and alleys marked by the daily practices of the working class, which in turn reject high modernization. Thus, it is precisely with the objective of investigating Porto do Capim as a space for workers that this dissertation is structured. For this purpose, based on the theoretical-methodological propositions of "history from below" and, more specifically, of the English historian E. P. Thompson (1981, 1987, 1997, 1998 and 2001), we analyzed some historical sources, notably newspapers and periodicals (O Norte, O Jornal, A União and Diário de Pernambuco), photographs (Acervo do Porto de Cabedelo) and various documents from the State and private business associations, such as telegrams from the Commercial Association of Paraíba, Reports from the President of the Province of Paraíba, Reports on Transport and Public Works in Paraíba and the Code of Postures of the City of Parahyba do Norte. Through the crossing of sources and bibliographic materials, our analysis advanced in a series of considerations about Porto do Capim and the working class linked to it, as well as listing other points for the development of future investigations. In this sense, it aims to be another historiographic contribution to the historical understanding of class conflicts experienced in urban modernization processes, often concealed in hegemonic discourses of historical cultures that disregard their effects on subaltern classes. Specifically, this dissertation dialogues with the concerns of the History and Regionalities research line of the PPGH-UFPB, by addressing these issues as linked to political choices about the (re)definition of Paraíba in the global capitalist circuit.